FUNGSI PEMBINAAN LURAH TERHADAP RUKUN TETANGGA DAN RUKUN WARGA DI KELURAHAN TANGKERANG TENGAH KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU TAHUN 2013-2014 - Hastona, Ichwann; Ridwan, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The chief role is very important in a region, especially for the community, Based on Government Regulation Number 73 Year 2005 about Ward article 5 , one of the main tasks village that is doing construction of a society that is RW and RT. The existence of his neighbor community and Pillars of the (RW) have a strategic role, especially as a partner in the event district government affairs, development and community affairs. What about the function headman to the village of his neighbor and Pillars of residents in the village Tangkerang among sub-district Marpoyan Peace Pekanbaru in 2013-2014?Research method that is applied in this study is descriptive qualitative analysis method that is trying to present based on the phenomena that are and to all the facts related to problems that were discussed, namely to know the construction of the village of Pillars of neighbors and Pillars of residents in the village Tangkerang among sub-district Marpoyan Peace Pekanbaru in 2013-2014.Results of the study showed fungsi construction of the village of Pillars of neighbors and Pillars of residents In the village Tangkerang among sub-district Marpoyan Peace Pekanbaru in 2013-2014 according to the writer is not optimal done with good, where construction of the village in the planning community institutional village RW and RT is in line with what was planned, however, RW on the development of organization and RT did not give administration report regularly to the chief, so that the chief did not carry out the supervision institutional village community RW and RT.Key words : function, headman, village of his neighbor, pillars of its neighbors.